Respon Perkembangan Dan Produksi Bawang Merah (Allium Ascalonicum L.) Dengan Aplikasi Jumlah Bibit Dan Pupuk Kandang Sapi - Aprilia Nur Fadila; Nunuk Helilusiatingsih; Titik Irawati (Berkala Ilmiah Pertanian, 2023)
Shallots have the potential to be cultivated in Kediri because they suit the growing environment. The problems include the level of awareness of farmers regarding excessive use of inorganic fertilizers and the number of seeds used in shallot cultivation. The aim of the research is to study and measure the response to development and production by treating the number of seeds and administering cow manure. The method uses a factorial randomized block design with two factors. The first factor is the dose of cow manure (P) with 3 levels, namely (P0 = 0gr/polybag, P1 = 150gr/polybag, and P2 = 250gr/polybag). The second factor is the number of seeds (J) consisting of 3 levels, namely (J1 = 1 seed/polybag, J2 = 2 seeds/polybag, and J3 = 3 seeds/polybag). The data obtained was continued with statistical tests with the BNT 5% or DMRT 5% test. Based on the research results, there was no interaction between the treatment dose of cow manure and the number of seeds per polybag. However, there was a real effect on the single treatment of cow manure during the vegetative period on plant height (42 DAP), namely P2, namely 32.39 cm/polybek, number of leaves, namely J3, there were 39.1 leaves,/polybek Generative vase on the best number of tubers parameters. P2 with a total of 14.2/polybag and wet weight on P2 with a weight of 48.02 grams/polybag